Preguntas más Frecuentes sobre 4-H - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H-FS-101.11-Spn, a 3-page fact sheet by Marilyn N. Norman and Joy C. Jordan, is the Spanish language version of 4H-FS-101.11: 4-H FAQs. It answers frequently asked questions about 4-H, such as “What happens in a 4-H club?” and “What is the 4-H Pledge?” Published by the UF 4-H and Youth Development Program, July 2009.